Identification of a novel small-molecule inhibitor of miR-29b attenuates muscle atrophy - Qi Liu; Weilin Yuan; Yuwei Yan; Bing Jin; Mengke You; Tianqi Liu; Mingchun Gao; Jin Li; Priyanka Gokulnath; Gururaja Vulugundam; Guoping Li; Bin Xu; et al. (Elsevier, 2023)
Muscle atrophy is debilitating and can be induced by several stressors. Unfortunately, there are no effective pharmacological treatment until now. MicroRNA (miR)-29b is an important target that we identified to be commonly involved in multiple types of muscle atrophy. Although sequence-specific inhibition of miR-29b has been developed, in this study, we report a novel small-molecule miR-29b inhibitor that targets miR-29b hairpin precursor (pre-miR-29b) (Targapremir-29b-066 [TGP-29b-066]) considering both its three-dimensional structure and the thermodynamics of interaction between pre-miR-29b and the small molecule. This novel small-molecule inhibitor has been demonstrated to attenuate muscle atrophy induced by angiotensin II (Ang II), dexamethasone (Dex), and tumor necrosis factor α (TNF-α) in C2C12 myotubes, as evidenced by increase in the diameter of myotube and decrease in the expression of Atrogin-1 and MuRF-1. Moreover, it can also attenuate Ang II-induced muscle atrophy in mice, as evidenced by a similar increase in the diameter of myotube, reduced Atrogin-1 and MuRF-1 expression, AKT-FOXO3A-mTOR signaling activation, and decreased apoptosis and autophagy. In summary, we experimentally identified and demonstrated a novel small-molecule inhibitor of miR-29b that could act as a potential therapeutic agent for muscle atrophy.